Positive electrode material, positive electrode plate and secondary battery
By introducing micropowder-like particles with bimodal particle size distribution into the positive electrode material of lithium-ion batteries, the powder conductivity and compaction density are improved, and the problem of insufficient performance of existing positive electrode materials is solved, thereby achieving higher capacity, lower resistance and excellent cycling performance.
Patent Information
- Application Number
- CN202411986916.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The ionic conductivity of the existing lithium-ion battery positive electrode materials is relatively low, resulting in poor battery capacity and rate performance and needs improvement.
A positive electrode material is provided, and its particle size number distribution curve is characterized by bimodal characteristics, including two peaks of 0~2μm and 1μm~6μm, and the powder conductivity under 6T pressure reaches T>0.015S/cm.
By increasing the powder conductivity of the positive electrode material, reducing the resistance and power consumption of the battery, improving the efficiency of energy transmission, and solving problems such as increasing surface side reactions and gas production caused by uncontrollable number of microparticles, improving safety and cycling performance.
Smart Images

Figure CN119650688A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] In line with the development trend of new energy, the large-scale deployment of electric vehicles and power storage systems has led to a sharp increase in global demand for lithium-ion batteries due to their high energy density and power density. Positive electrode materials are the core components of lithium-ion batteries and play a critical role in the cycle stability and capacity of lithium-ion batteries. However, the ionic conductivity of existing positive electrode materials is low, and the capacity and rate performance of the prepared batteries are poor, which urgently needs to be improved. Summary of the invention
[0003] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.
[0004] In addition, it is also necessary to provide a positive electrode sheet and a secondary battery using the above-mentioned positive electrode material.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode material, wherein a particle size number distribution curve of the positive electrode material comprises a first peak and a second peak, wherein the first peak is located between 0 and 2 μm, the second peak is located between 1 μm and 6 μm, and the position of the first peak is located on the left side of the second peak; the powder conductivity T of the positive electrode material under a pressure of 6 T satisfies: T>0.015 S / cm.
[0006] In some possible embodiments, the ratio of the peak intensity of the first peak to that of the second peak is ≥1.5; and / or the ratio of the peak area of the first peak to that of the second peak is 0.1-1.
[0007] In some possible embodiments, the powder conductivity T of the positive electrode material under a pressure of 6T satisfies: 0.015S / cm<T<0.05S / cm.
[0008] In some possible embodiments, the intensity ratio of the first peak to the second peak is 1.5-4.
[0009] In some possible embodiments, the XRD diffraction pattern of the positive electrode material includes a 003 peak and a 104 peak, and the ratio of the peak intensities of the 003 peak and the 104 peak is 1.1-1.8.
[0010] In some possible embodiments, the general formula of the positive electrode material is as follows: Li a Ni x M y N 1-x-y O b, wherein 0.98≤a≤1.05, 0.60≤x<1, 0<y≤0.40, 0.95≤b≤1.05, the M element is selected from at least one of Co, Mn, and Al, and the N element is selected from at least one of Ti, Zr, Mg, Sr, Ba, Nb, W, and Y.
[0011] In some possible embodiments, in the volume particle size distribution of the positive electrode material, D50 is 2.5 μm to 5.5 μm, Dmin>0.1 μm, and Dmax<14 μm; In some possible embodiments, the particle size volume distribution width of the positive electrode material is 1.0~2.6; In some possible embodiments, the specific surface area of the positive electrode material is 0.6 m 2 / g~1.2m 2 / g; In some possible embodiments, the compaction density of the positive electrode material is greater than 3.0 g / cm 3 ; In some possible embodiments, the powder resistivity of the positive electrode material under a pressure of 6T is less than 6666.66Ω·m.
[0012] In some possible embodiments, the positive electrode material is a single crystal material, the positive electrode material contains single grains with the same orientation, and the average grain size of the single grains is 1 μm to 6 μm.
[0013] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described above or a positive electrode material prepared by the positive electrode material preparation method as described above.
[0014] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0015] The positive electrode material provided in the embodiment of the present application obtains a higher powder conductivity (powder conductivity T>0.015S / cm under a pressure of 6T) through the positive electrode material. The higher powder conductivity makes the positive electrode material have good electrical conductivity, effectively reduces the resistance and power consumption of the prepared battery, and improves the efficiency of energy transmission. However, the higher the powder conductivity of the positive electrode material, the more active sites there are inside the material, and too many active sites will lead to a large number of side reactions. To this end, the embodiment of the present application limits the particle size distribution curve of the positive electrode material to present the above bimodal characteristics, wherein the introduction of a controllable number of micro-powder particles enables the positive electrode material to have the advantages of high compaction density and high material activity at the same time, and solves the problems faced by the existing positive electrode materials, such as the uncontrollable number of microparticles leading to increased surface side reactions and increased gas production, thereby improving safety and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0017] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0018] Figure 3 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 1 of the present application.
[0019] Figure 4 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 2 of the present application.
[0020] Figure 5 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 3 of the present application.
[0021] Figure 6 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 4 of the present application.
[0022] Figure 7 This is the particle size distribution curve of the positive electrode material of Example 1 of the present application. DETAILED DESCRIPTION
[0023] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0024] The present application embodiment provides a positive electrode material, wherein the particle size number distribution curve of the positive electrode material includes a first peak and a second peak, the first peak is between 0 and 2 μm, the second peak is between 1 μm and 6 μm, the first peak is located on the left side of the second peak; and the powder conductivity T of the positive electrode material satisfies: T>0.015 S / cm. In some embodiments, the first peak may be between 0.1 and 2 μm.
[0025] A higher powder conductivity (powder conductivity T>0.015S / cm at a pressure of 6T) is obtained through the positive electrode material. The higher powder conductivity makes the positive electrode material have good electrical conductivity, effectively reduces the resistance and power consumption of the prepared battery, and improves the efficiency of energy transmission. However, the higher the powder conductivity of the positive electrode material, the more active sites there are inside the material, and too many active sites will lead to a large number of side reactions. To this end, the embodiment of the present application limits the particle size distribution curve of the positive electrode material to present the above bimodal characteristics, wherein the introduction of a controllable number of micro-powder particles enables the positive electrode material to have the advantages of high compaction density and high material activity at the same time, and solves the problems faced by the existing positive electrode materials, such as the uncontrollable number of microparticles leading to increased surface side reactions and increased gas production, thereby improving safety and cycle performance. In addition, the inventors have found through a large number of experimental studies that when the particle size distribution curve of the positive electrode material presents the above bimodal characteristics, the volume change of the positive electrode material during the charge and discharge process is small. The inventors speculate that this is because the particles in the micro-powder state can act as a buffer in the positive electrode material, play a role in dispersing stress, and suppress the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material. Therefore, the high compaction and high ionic conductivity brought about by the high packing density of the positive electrode material of the present application complement each other, so that the battery prepared by the positive electrode material has both high capacity and energy transmission efficiency, low resistance and power consumption, and excellent cycle performance.
[0026] Further, the powder conductivity T of the positive electrode material satisfies: 0.015S / cm<T<0.05S / cm. Exemplarily, the powder conductivity of the positive electrode material may be 0.016S / cm, 0.018S / cm, 0.02S / cm, 0.025S / cm, 0.03S / cm, 0.035S / cm, 0.04S / cm, 0.045S / cm, 0.05S / cm, or any value within the range formed by any two of the above values.
[0027] In some embodiments, the intensity ratio of the first peak to the second peak is ≥1.5, indicating that the second peak in the positive electrode material is relatively shorter and more rounded, which conforms to the normal distribution, while the first peak is narrower and taller, indicating that the first peak is a narrow distribution width of particles in a micro-powder state, and the particle size of particles in a micro-powder state is relatively uniform. Further, the intensity ratio of the first peak to the second peak is 1.5-4. Exemplarily, the intensity ratio of the first peak to the second peak can be 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.3, 3.5, 4 or any value within the range of any two of the above values.
[0028] In some embodiments, in the particle size distribution curve of the positive electrode material, the ratio of the peak area of the first peak to the second peak is 0.1-1, that is, the peak area of the first peak is less than or equal to the peak area of the second peak. This indicates that the number of particles of 0-2 μm is less than or equal to the number of particles of 1-6 μm, that is, the proportion of small particles is less than or equal to the proportion of large particles, and the particle size distribution is wide, which is conducive to further realizing the close stacking of positive electrode materials to improve the compaction density of positive electrode materials, and further increase the role of small particles in dispersing stress, reduce the local stress concentration of large particles during volume change, thereby increasing the structural stability of the positive electrode material and improving the cycle performance of the positive electrode material.
[0029] In some embodiments, the particle size number distribution width of the first peak is Span(b), which satisfies 0.4<Span(b)<1.8. Specifically, it can be 0.81, 0.85, 0.89, 0.92, 0.98, 1.01, 1.05, 1.2, 1.25, 1.3, 1.39, 1.4, 1.42, 1.45, 1.5, 1.57 or 1.63, etc., which are not limited here. Preferably, 0.8<Span(b)<1.4 is satisfied.
[0030] In some embodiments, the particle size number distribution width of the second peak is Span(a), which satisfies 0.8<Span(a)<1.64; specifically, it can be 0.41, 0.42, 0.45, 0.58, 0.62, 0.7, 0.72, 0.75 or 0.795, etc., which is not limited here.
[0031] In some embodiments, the peak value percentage of the first peak is 0.15% to 0.2%. Specifically, it can be 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.20%, etc. The peak value percentage of the second peak is 0.05% to 0.13%. Specifically, it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12% or 0.13%, etc.
[0032] In some embodiments, the XRD diffraction pattern of the positive electrode material includes a 003 peak and a 104 peak, and the peak intensity ratio of the 003 peak to the 104 peak is 1.1-1.8, indicating that Li + / Ni 2+ The proportion of mixed arrangement is moderate, and the above range of Li + / Ni 2+ Mixing can improve the stability of the crystal structure and enhance the cyclic stability of the material, while also ensuring that the material has higher capacity and lower internal resistance.
[0033] In some embodiments, in the volume particle size distribution of the positive electrode material, the median particle size D50 is 2.5μm~5.5μm, Dmin>0.1μm, and Dmax<14μm. The volume median particle size D50 represents the particle size of the material particles corresponding to the cumulative particle size distribution percentage reaching 50% volume ratio. Dmin represents the smallest particle diameter in the volume particle size distribution. Dmax represents the largest particle diameter in the volume particle size distribution. The present application controls the median particle size of the positive electrode material within the above appropriate range, and the particle size is moderate, which is beneficial to control the specific surface area of the particles within a suitable range, improves the activity of the material, and reduces the side reactions between the particles and the electrolyte, thereby improving the cycle life of the battery. In addition, particles of the above range size are also beneficial to reduce the internal stress of the particles and reduce the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby improving the capacity of the positive electrode material. Illustratively, the median particle size D50 of the positive electrode material may be 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, or any value within the range formed by any two of the above values.
[0034] In some embodiments, the volume particle size distribution width Span value of the positive electrode material is 1.0~2.6, that is, 1.0≤(D90-D10) / D50≤2.6; D10 in the particle size distribution represents the particle size corresponding to when the volume cumulative particle size distribution reaches 10%. D90 represents the particle size corresponding to when the volume cumulative particle size distribution reaches 90%. (D90-D10) / D50 represents the width of the particle size distribution in the positive electrode material. In this application, by controlling 1.0≤(D90-D10) / D50≤2.6, the volume particle size distribution of the positive electrode material is wider, which can improve the compaction density and material activity of the material while reducing the side reaction between the material and the electrolyte, thereby ensuring that the positive electrode material has high compaction density, high material activity, low impedance and excellent cycle performance. Illustratively, the volume particle size distribution width (D90-D10) / D50 of the positive electrode material can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6 or any value within the range formed by any two of the above values.
[0035] In some embodiments, the specific surface area of the positive electrode material is 0.6 m 2 / g~1.2m 2 / g, the gaps between the large particles in the positive electrode material contain a certain number of small particles in a powder state, which can control the specific surface area within the aforementioned appropriate range, which is beneficial to improving the activity of the positive electrode material, while reducing the side reactions between the positive electrode material and the electrolyte, and improving the safety and cycle performance of the material while improving the conductivity of the positive electrode material. For example, the specific surface area of the positive electrode material can be 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9 m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g or any value within the range formed by any two of the above values.
[0036] In some embodiments, the compaction density of the positive electrode material is greater than 3.0 g / cm 3 By controlling the particle size distribution curve of the positive electrode material to have a bimodal feature, the particles of the positive electrode material are partially composed of small particles in the form of micro-powder. During the rolling process of the positive electrode material, under the action of external force, the small particles in the positive electrode material can fill the gaps in the large particles, thereby increasing the compaction density of the material and improving the capacity and cycle performance of the positive electrode material. For example, the compaction density of the positive electrode material can be 3.0 g / cm 3 、3.1g / cm 3 、3.15g / cm3 、3.2g / cm 3 , 3.25g / cm 3 、3.3g / cm 3 、3.4g / cm 3 Or any value within the range formed by any two of the above values. Further, the compaction density of the positive electrode material can be 3.1 g / cm 3 ~3.4g / cm 3 .
[0037] In some embodiments, the powder resistivity of the positive electrode material under a pressure of 6T is less than 6666.66Ω·m. Since the powder resistivity of the positive electrode material is inversely proportional to the powder conductivity, the positive electrode material with higher powder conductivity has better conductive properties and can effectively reduce the powder resistivity.
[0038] In some embodiments, the general formula of the positive electrode material is as follows: Li a Ni x M y N 1-x-y O b , wherein 0.98≤a≤1.05, 0.60≤x<1, 0<y≤0.40, 0.95≤b≤1.05, the M element is selected from at least one of Co, Mn, and Al, and the N element is selected from at least one of Ti, Zr, Mg, Sr, Ba, Nb, W, and Y.
[0039] The specific value of a can be 0.98, 0.99, 1.0, 1.02, 1.04 or 1.05, the specific value of x can be 0.6, 0.61, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98, etc., the value of y can be 0.01, 0.05, 0.08, 0.09, 0.1, 0.11, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.32, 0.35, 0.38 or 0.4, etc., the value of b can be 0.95, 0.98, 0.99, 1.0, 1.02, 1.04 or 1.05, etc., and there is no limitation on this.
[0040] In some embodiments, based on the mass of the positive electrode material, the content of the N element is 200ppm to 10000ppm. For example, the content of the N element can be 200ppm, 500ppm, 800ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm or any value within the range of any two of the above values.
[0041] The positive electrode material provided in the embodiment of the present application has a powder conductivity T>0.015S / cm of the positive electrode material under a pressure of 6T. The higher powder conductivity makes the positive electrode material have good electrical conductivity, effectively reduces the resistance and power consumption of the prepared battery, and improves the efficiency of energy transmission. Secondly, the present application also introduces controllable small particles in a micro-powder state by limiting the particle size distribution curve of the positive electrode material to present the above bimodal characteristics, so that the positive electrode material has the advantages of high compaction density and high material activity at the same time, and solves the problems of the uncontrollable number of particles in the micro-powder state faced by the existing positive electrode materials, resulting in an increase in surface side reactions and increased gas production, thereby improving safety and cycle performance. In addition, the small particles in the micro-powder state introduced can also be used as a buffer in the positive electrode material to disperse stress and suppress the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material. Therefore, the high compaction and high ionic conductivity brought by the high packing density of the positive electrode material of the present application complement each other, so that the battery prepared by the positive electrode material has both high capacity and energy transmission efficiency, low resistance and power consumption, and excellent cycle performance.
[0042] In some embodiments, the positive electrode material may be a single crystal material, the positive electrode material contains single grains with the same orientation, and the average particle size of the single grains is 1µm~6µm, and the grains are primary particles. The average particle size of the single grains is within the above range, which is beneficial to the transmission of lithium ions during charging and discharging, improves ionic conductivity and thus reduces impedance; at the same time, particles in the above particle size range can control the specific surface area within an appropriate range, improve the activity of the material while reducing the side reactions between the material and the electrolyte. Exemplarily, the average particle size of a single grain may be 1µm, 2µm, 3µm, 4µm, 5µm, 6µm, or any value within the range formed by any two of the above values.
[0043] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0044] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually 1μm~6μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".
[0045] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.
[0046] The present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, preparing an oxide precursor by spray pyrolysis.
[0047] Specifically, metal salt solutions of a nickel source, a cobalt source, a manganese source (or an aluminum source) and the like are mixed, and the mixture is atomized and then thermally decomposed to obtain an oxide precursor.
[0048] Since the reaction time of thermal decomposition after atomization is short, the diameter of the liquid droplets after atomization is very small, often less than 5μm, and the precursor formed is amorphous particles. In a short time, the dust collector in the equipment can collect a large number of small particles, making the porosity of the material smaller when it is stacked. This is also the main reason for the formation of the first peak (micro powder peak) in the particle size distribution curve of the positive electrode material.
[0049] In some embodiments, the metal salts of the nickel source, cobalt source, manganese source, and aluminum source may be sulfates, chlorides, nitrates, acetates, and the like of the corresponding metal elements.
[0050] In some embodiments, a metal salt solution of element N, at least one of the elements Ti, Zr, Mg, Sr, Ba, Nb, W and Y, may be added to the mixture.
[0051] In some embodiments, the pressure at the nozzle mouth can be 2.5MPa~40MPa. During the spray pyrolysis process, the atomization intensity can be controlled by controlling the pressure at the nozzle mouth, and then the particle size of the generated precursor particles can be controlled. By controlling the pressure at the nozzle mouth within the aforementioned range, the particle size distribution curve of the precursor can be made to present a bimodal feature, and micro-powdered small particles are introduced into the main particles. Since the particle size of the precursor prepared by the present application method has good inheritance, the particle size distribution curve of the positive electrode material can also present a bimodal feature by controlling the particle size distribution of the precursor. Exemplarily, the pressure at the nozzle mouth can be 2.5MPa, 3.0MPa, 3.5MPa, 4.0MPa, 5.0MPa, 8.0MPa, 10MPa, 15MPa, 20MPa, 25MPa, 30MPa, 35MPa, 40MPa or any value within the range composed of any two of the above values.
[0052] In some embodiments, the nozzle diameter can be 0.1 mm to 10 mm. By controlling the nozzle diameter, the formation rate of the precursor and the particle size of the primary particles can be further regulated, and the particle size distribution curve of the precursor can be further controlled to present a bimodal feature. Exemplarily, the nozzle diameter can be 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, or any value within the range of any two of the above values.
[0053] In some embodiments, the ratio of the nozzle pressure to the nozzle diameter (i.e., the pressure-to-diameter ratio) can be 1 MPa / mm to 60 MPa / mm, and the pressure-to-diameter ratio can be adjusted within the aforementioned range to generate atomized droplets to control the peak position, peak height, and peak width of the first peak. Exemplarily, the pressure-to-diameter ratio can be 1 MPa / mm, 3 MPa / mm, 5 MPa / mm, 8 MPa / mm, 10 MPa / mm, 13 MPa / mm, 15 MPa / mm, 18 MPa / mm, 20 MPa / mm, 25 MPa / mm, 30 MPa / mm, 35 MPa / mm, 40 MPa / mm, 45 MPa / mm, 50 MPa / mm, 55 MPa / mm, 60 MPa / mm, or any value within the range formed by any two of the above values.
[0054] In some embodiments, the spray concentration of the mixed solution is controlled to be 0.5 L / m 3 ~4L / m 3 By controlling the spray concentration of the solution within the above range, the particle size of the primary particles of the oxide precursor can be controlled, so that the particle size distribution of the primary particles of the precursor is wider, which is conducive to the formation of micro-powder particles in the positive electrode material, and thus the particle size number distribution curve of the precursor presents a bimodal feature. For example, the spray concentration of the mixed solution can be 0.5L / m 3 , 1L / m 3 , 1.5L / m 3 , 2L / m 3 , 2.5L / m 3 , 3L / m 3 、3.5L / m 3 , 4L / m 3 Or any value within the range formed by any two of the above values.
[0055] In some embodiments, the pyrolysis temperature is controlled to be 550°C to 1050°C. Since the uncontrollable small particles in the micro-powder state in the positive electrode material will lead to an increase in side reactions on the surface of the material, for this reason, the present application can appropriately suppress the increase in the particle size of the precursor primary particles by regulating the pyrolysis temperature within the above range, so that the activity of the primary particles is enhanced, and particles with larger particle sizes are formed when reacting with lithium salts, thereby suppressing the formation of small particles in the micro-powder state to a certain extent, so as to achieve the purpose of regulating the proportion of small particles in the micro-powder state in the positive electrode material, realize the controllable number of small particles in the micro-powder state, and improve the activity of the positive electrode material while reducing the occurrence of side reactions.
[0056] Step S2, mixing the oxide precursor with the lithium source and the dopant and sintering (defined as primary sintering here) to obtain a positive electrode material matrix.
[0057] In this step, the primary sintering is a two-stage sintering, including a first sintering stage and a second sintering stage performed sequentially, after which the temperature is lowered to room temperature at a certain rate (eg, 1.0°C / min to 5.0°C / min) to obtain a positive electrode material matrix.
[0058] In some embodiments, the temperature T1 of the first sintering stage is 700°C~950°C, and the time is 0~8h. Firstly, the material is heated to the above temperature stage, so that the lithium salt can be fully melted, the dopant can be evenly diffused in the mixture, and the lithium ions can be embedded, which can promote the growth of crystals and control the growth rate and size of the particle size of the crystal particles. In this stage, many crystal nuclei can be produced, particles in a micro-powder state can be shaped, and favorable conditions are provided for creating the first peak (micro-powder peak) of the double peak curve of the precursor, which is conducive to the formation of double peak characteristics. Exemplarily, the temperature of the first sintering stage can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or any value in the range composed of any two of the above values; the sintering time can be 0h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value in the range composed of any two of the above values.
[0059] In some embodiments, the temperature T2 of the second sintering stage is 800°C~1050°C, and the time is 6h~16h. This stage is a further growth stage of the crystal. By controlling the sintering temperature and sintering time within the above range, the embedding of lithium ions can be achieved, the growth of the crystal can be promoted, and the particle size of the crystal particles can be controlled to form a double peak feature with the first peak at 0~2μm and the second peak at 1μm~6μm. Exemplarily, the temperature of the second sintering stage can be 800°C, 900°C, 950°C, 1000°C, 1050°C or any value in the range composed of any two of the above values; the sintering time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h or any value in the range composed of any two of the above values.
[0060] In some embodiments, the sintering atmosphere may be an oxygen atmosphere or an air atmosphere.
[0061] In this step, the lithium source can be added in batches. Specifically, the lithium source can be added in batches in the first sintering stage and the second sintering stage. Adding the lithium source in batches can make the lithium source melt more fully and embed into the crystal to control the growth rate and particle size of the crystal, thereby forming a precursor with the aforementioned double peak characteristics.
[0062] In some embodiments, the molar ratio of the lithium source added in the first sintering stage to the precursor is 0.1-0.6, and the molar ratio of the lithium source added in the second sintering stage to the precursor is 0.4-0.9. Adding the lithium source in batches can make the lithium source melt more fully and embed into the crystal. It is understandable that the lithium source can also be added all at once.
[0063] In some embodiments, the lithium source may be at least one of LiOH·H2O, Li2CO3, LiCl, Li2SO4, LiNO3, and LiCH3COO.
[0064] In some embodiments, the molar ratio of the lithium content in the lithium salt to the nickel, cobalt and manganese content in the precursor is 0.98 to 1.10.
[0065] In this step, the doping element N in the dopant is selected from at least one of Ti, Zr, Mg, Al, Sr, Ba, Nb, W and Y. The dopant can be an oxide, hydroxide, carbonate, oxyhydroxide, etc. of the aforementioned doping element.
[0066] In some embodiments, the content of the dopant is 200 ppm to 10000 ppm. For example, the content of the dopant is 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm or any value in the range consisting of any two of the above values.
[0067] Step S3, crushing the cathode material matrix and coating it with a coating agent to obtain the cathode material. The obtained cathode material has a particle size distribution curve including a first peak and a second peak, the first peak is between 0 and 2 μm, the second peak is between 1 μm and 6 μm, and the first peak is located on the left side of the second peak; and the powder conductivity T of the cathode material satisfies: T>0.015 S / cm.
[0068] Specifically, the positive electrode material matrix obtained by the previous sintering step is crushed, and the particle size of the matrix is adjusted by controlling the process parameters of the airflow crushing, so that the particle size D50 of the positive electrode material matrix is 2.5μm~5.5μm.
[0069] The crushed positive electrode material matrix is coated once to obtain a primary coated material, and the primary coated material is coated twice, screened and ground to finally obtain the positive electrode material. After two coating and sintering, the coating agent can be evenly coated on the surface of the positive electrode material matrix for surface modification, so as to further improve the structural stability and electrochemical performance of the positive electrode material.
[0070] In some embodiments, the coating element of the primary coating includes at least one of Al, Zr, Nb, W, Co and Mn, etc. The first coating agent of the primary coating may be an oxide or hydroxide of the aforementioned coating element.
[0071] In some embodiments, the content of the coated element of the primary coating can be 500ppm~3000ppm. Exemplarily, the content of the coated element of the primary coating can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm or any value within the range composed of any two of the above values.
[0072] In some embodiments, the content of the coating element of the secondary coating can be 300ppm~1800ppm. Exemplarily, the content of the coating element of the secondary coating can be 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm or any value within the range consisting of any two of the above values.
[0073] In some embodiments, the coating element of the secondary coating includes at least one of Al, Ti, W, B, Mg, Ca, Nb and P.
[0074] In some embodiments, the second coating agent of the secondary coating includes at least one of Al2O3, ZrO2, Nb2O5, WO3, CoO, and MnO2.
[0075] In some embodiments, the coating agent of the second coating includes at least one of Al2O3, TiO2, WO3, B2O3, Mg(OH)2, CaO, Nb2O5, and P2O3.
[0076] In some embodiments, the sintering temperature of the primary coating is 600-900°C, and the sintering time can be 4-12 hours. For example, the sintering temperature of the primary coating can be 600°C, 700°C, 800°C, 900°C, or any value in the range consisting of any two of the above values, and for example, the sintering time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, or any value in the range consisting of any two of the above values.
[0077] In some embodiments, the sintering temperature of the secondary coating may be 300° C. to 600° C., and the sintering time may be 3 h to 9 h. For example, the sintering temperature of the secondary coating may be 300° C., 400° C., 500° C., 600° C., or any value in the range of any two of the above values, and the sintering time may be 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or any value in the range of any two of the above values.
[0078] By controlling the temperature and time of the primary coating and the secondary coating, the coating agent can be evenly coated on the surface of the substrate in batches, further optimizing the surface structure of the positive electrode material, so as to further improve the structural stability and conductivity of the positive electrode material.
[0079] Since the diameter of the liquid droplets after the precursor solution is atomized is very small, often less than 5μm, the pyrolysis reaction process is short, and the dust collector can collect a large number of small particles in a short time, so that the material has a smaller porosity and a larger stacking density when stacked, so that the positive electrode material has a higher compaction density. Moreover, unlike the hydroxide precursor, the oxide precursor has a certain crystal structure and is a two-phase mixture of spinel and rock salt phases. The oxide precursor has a larger diffusion width when sintering with the lithium salt, and the relatively wider particle size distribution is conducive to the formation of micro-powder particles with an appropriate number of proportions. In other words, the particle size distribution of the prepared oxide precursor is wider, and the reaction activity with the lithium salt is lower, so that the crystal particles are not fully diffused when growing into single crystals. The degree of single crystallization of some particles is not enough to form micro-powder particles with smaller particle size. By controlling the width of the particle size distribution of the aforementioned oxide precursor, the particle size distribution curve of the positive electrode material with the aforementioned double peak characteristics can be controlled during the sintering process. Moreover, the particle size distribution of the positive electrode material has good inheritance. The positive electrode material can well inherit the particle size distribution of the matrix, and the matrix can also well inherit the particle size distribution of the oxide precursor to a certain extent.
[0080] Secondly, close agglomeration is conducive to better combination of precursor and conductive agent, reducing the proportion of micropores in the material, greatly improving the conductivity of the active material of the positive electrode material, and the higher compaction density also reduces the transmission path of lithium ions, thereby effectively reducing the ionic conductivity of the positive electrode material. In addition, by sintering at multiple temperature stages to allow the oxide precursor to fully react with the lithium salt added in batches, the formation of micro-powder particles can be further controlled, which is conducive to the particle size distribution curve of the formed positive electrode material showing the aforementioned double peak characteristics.
[0081] In addition, the preparation method of the embodiment of the present application has a short reaction time, has the advantages of short-range high efficiency, low processing cost, low raw material cost, less pollution, no wastewater generation, and high recycling rate, etc., and is suitable for industrial large-scale production.
[0082] An embodiment of the present application also provides a positive electrode sheet using the aforementioned positive electrode material, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode material.
[0083] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0084] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0085] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0086] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0087] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0088] The secondary battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0089] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.
[0090] The embodiment of the present application adopts the aforementioned positive electrode material to prepare a secondary battery, and controls the particle size distribution curve of the positive electrode material to present a bimodal feature. The introduction of certain micro-powder particles can enhance the charge transfer effect, reduce the internal resistance of the secondary battery, and achieve the improvement of conductivity. The powder conductivity T of the positive electrode material under 6T pressure is greater than 0.015S / cm, so that the positive electrode material has both high compaction density and high material activity, improves the capacity and cycle performance of the secondary battery, and reduces the internal resistance of the secondary battery. The capacity of the secondary battery using the aforementioned positive electrode material is greater than 200mAh / g, the first cycle coulomb efficiency is greater than 90%; the 50-cycle capacity cycle retention rate is greater than 94%, and the 2C capacity retention rate is greater than 86%; the low-temperature DCR is less than 126Ω, and the high-temperature DCR growth rate is less than 11%.
[0091] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0092] Embodiment 1: Step 1: prepare a sulfate mixed solution of Ni, Co and Mn in a ratio of 62.5:12:26.5, and control the total metal concentration in the mixed solution to be 0.005 mol / L; spray the mixed solution into a pyrolysis tower for pyrolysis, control the nozzle pressure to be 3.5 MPa, the nozzle diameter to be 1 mm, and control the spray concentration in the tower to be 0.5 L / m 3 The pyrolysis temperature is 750℃, and the precursor Ni 0.625 Co 0.12 Mn 0.265 O x (0.5<X<1.5).
[0093] Step 2, weighing the precursor and the lithium source (Li2CO3) for sintering, wherein, the first sintering stage: mixing a portion of the lithium source with the precursor at a molar ratio of 0.6:1, after mixing evenly, sintering in an air atmosphere at a sintering temperature of 900°C, a sintering time of 4 hours, and taking out the intermediate product; the second sintering stage: mixing the remaining lithium source with the intermediate product at a molar ratio of 0.403:1 of the lithium source to the precursor, after mixing evenly, sintering in an oxygen atmosphere at a sintering temperature of 950°C, a sintering time of 8 hours, and then cooling to room temperature at a rate of 1.5°C / min to obtain a positive electrode material matrix.
[0094] Step 3, weigh the positive electrode material matrix, the first coating agent MnO2 and the first coating agent Al(OH)3 respectively according to the mass ratio of 1:0.018:0.005, mix them thoroughly, place them in an atmosphere furnace, keep them at 800℃ for 5h, and then cool them to room temperature to obtain a primary coating product.
[0095] Step 4: The primary coating product is fully dissociated by a stone mill, and the primary coating product and the second coating agent WO3 are weighed in a mass ratio of 1:0.05, mixed evenly, and transferred to an atmosphere furnace for heat treatment at 550°C for 5h. The positive electrode material is obtained, and the chemical formula is LiNi 0.625 Co 0.12 Mn 0.265 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0096] Example 2 The difference from Example 1 is that in step 1, the nozzle opening pressure is controlled to be 3 MPa and the nozzle opening diameter is controlled to be 2 mm.
[0097] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0098] Example 3 The difference from Example 1 is that in step 1, the nozzle opening pressure is controlled to be 20 MPa and the nozzle opening diameter is 0.5 mm.
[0099] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0100] Example 4 The difference from Example 1 is that in step 2, the first sintering stage: a part of the lithium source and the precursor are mixed in a molar ratio of 0.5:1, and after mixing evenly, they are sintered in an air atmosphere at a sintering temperature of 950°C and a sintering time of 4 hours to obtain an intermediate product; the second sintering stage: the remaining lithium source and the intermediate product are mixed in a molar ratio of 0.503:1 to the precursor, and after mixing evenly, they are placed in an oxygen atmosphere for sintering at a sintering temperature of 950°C and a sintering time of 8 hours.
[0101] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0102] Example 5 The difference from Example 1 is that in step 1, the sulfates of Ni, Co, and Mn are prepared into a sulfate mixed solution in a ratio of 94:5:1, and the total metal concentration in the mixed solution is controlled to be 0.005 mol / L, and finally the precursor Ni is obtained. 0.94 Co 0.05 Mn 0.01 O x (0.5<X<1.5).
[0103] In step 2, the first sintering stage: a portion of the lithium source and the precursor are mixed according to a molar ratio of 0.5:1, and after mixing evenly, they are sintered in an air atmosphere at a sintering temperature of 750°C and a sintering time of 4 hours to obtain an intermediate product; the second sintering stage: the remaining lithium source and the intermediate product are mixed according to a molar ratio of 0.503:1 of the lithium source and the precursor, and after mixing evenly, they are placed in an oxygen atmosphere for sintering at a sintering temperature of 800°C and a sintering time of 8 hours. The chemical formula of the positive electrode material obtained is LiNi 0.94 Co 0.05 Mn 0.01 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0104] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0105] Example 6 The difference from Example 1 is that in step 1, the nitrates of Ni, Co, and Mn are prepared into a nitrate mixed solution in a ratio of 82.5:6.5:11, and the total metal concentration in the mixed solution is controlled to be 0.005 mol / L, and finally the precursor Ni 0.825 Co 0.065 Mn 0.11 O x (0.5<X<1.5).
[0106] In step 2, the first sintering stage: a portion of the lithium source and the precursor are mixed according to a molar ratio of 0.5:1, and after mixing evenly, they are sintered in an air atmosphere at a sintering temperature of 950°C and a sintering time of 4 hours to obtain an intermediate product; the second sintering stage: the remaining lithium source and the intermediate product are mixed according to a molar ratio of 0.503:1 of the lithium source and the precursor, and after mixing evenly, they are placed in an oxygen atmosphere for sintering at a sintering temperature of 950°C and a sintering time of 8 hours. The chemical formula of the positive electrode material obtained is LiNi 0.825 Co 0.065 Mn 0.11 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0107] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0108] Example 7 The difference from Example 1 is that the second coating agent in step 4 is changed to TiO2.
[0109] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0110] Example 8 The difference from Example 1 is that in step 1, the chloride salts of Ni, Co and Mn are prepared into a chloride salt mixed solution in a ratio of 94:5:1, and the total metal concentration in the mixed solution is controlled to be 0.020 mol / L, and finally the precursor Ni 0.94 Co 0.05 Mn 0.01 O x (0.5<X<1.5).
[0111] In step 2, the first sintering stage: a portion of the lithium source and the precursor are mixed according to a molar ratio of 0.5:1, and after mixing evenly, they are sintered in an air atmosphere at a sintering temperature of 750°C and a sintering time of 4 hours to obtain an intermediate product; the second sintering stage: the remaining lithium source and the intermediate product are mixed according to a molar ratio of 0.503:1 of the lithium source and the precursor, and after mixing evenly, they are placed in an oxygen atmosphere for sintering at a sintering temperature of 800°C and a sintering time of 8 hours. The chemical formula of the positive electrode material obtained is LiNi 0.94 Co 0.05 Mn 0.01 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0112] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0113] Example 9 The difference from Example 1 is that in step 3, the positive electrode material matrix, the first coating agent CoO(OH) and the first coating agent Al(OH)3 are weighed respectively in a mass ratio of 1:0.018:0.005, and after being fully mixed, placed in an atmosphere furnace, sintered at 800°C for 5h, and then cooled to room temperature to obtain a primary coating product.
[0114] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0115] Example 10 The difference from Example 9 is that in step 4, the temperature of the secondary coating is 430°C.
[0116] The other steps are basically the same as those in Example 9, please refer to Example 9.
[0117] Embodiment 11 The difference from Example 1 is that in step 1, the sulfates of Ni, Co, and Al are prepared into a sulfate mixed solution in a ratio of 72.5:15:12.5, and the total metal concentration in the mixed solution is controlled to be 0.005 mol / L, and finally the precursor Ni 0.725 Co 0.15 Al 0.125 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0118] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0119] Example 12 The difference from Example 1 is that the sintering temperature in the first stage of step 2 is 830°C; the sintering temperature in the second stage is 925°C The other steps are basically the same as those in Example 1, please refer to Example 1.
[0120] Embodiment 13 The difference from Example 1 is that in step 2, the first stage sintering temperature is 730°C; and the second stage sintering temperature is 900°C.
[0121] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0122] Embodiment 14 The difference from Example 11 is that in step 1, the sulfates of Ni, Co, Al, Zr, Sr and Nb are prepared into a sulfate mixed solution in a ratio of 72.5:15:12.5:0.2:0.1:0.1, and the total metal concentration in the mixed solution is controlled to be 0.005 mol / L, and finally the precursor Ni is obtained. 0.725 Co 0.15 Al 0.125 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0123] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0124] Embodiment 15 The difference from Example 1 is that in step 1, the soluble sulfates of Ni, Co, Mn and Y are prepared into a sulfate mixed solution in a ratio of 62.5:12:26.5:0.3, and the total metal concentration in the mixed solution is controlled to be 0.005 mol / L, and finally the precursor Ni 0.725 Co 0.15 Mn 0.125 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0125] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0126] Example 16 The difference from Example 1 is that in step 3, the first coating agent MnO2 and the first coating agent Al(OH)3 are not added, and in step 4, the second coating agent WO3 is not added.
[0127] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0128] Embodiment 17 The difference from Example 1 is that in step 1, the nozzle diameter is controlled to be 5 mm.
[0129] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0130] Comparative Example 1 Step 1: weigh 1 kg of single crystal ternary precursor Ni prepared by coprecipitation method. 0.60 Co 0.10 Mn 0.30 O x (0.5<X<1.5), 503.6g lithium carbonate, after mixing evenly, heat-treat at 900℃ in oxygen atmosphere for 10h to obtain an intermediate product.
[0131] Step 2, weigh 300 g of the intermediate product and 10 g of cobalt oxide, mix them thoroughly, place them in an atmosphere furnace, keep them at 800° C. for 5 h, and then cool them to room temperature to obtain a positive electrode material matrix.
[0132] Step 3: After the above cathode material matrix is fully dispersed with a mixer, 200 g of the cathode material matrix is mixed with 2 g of boric acid, transferred to an atmosphere furnace, and heat treated at 550 ° C for 5 h to obtain a cathode material LiNi 0.60 Co 0.10 Mn 0.30 O x (0.5<X<1.5), where the amount of doping elements and coating elements is difficult to determine accurately and is not reflected in the chemical formula.
[0133] Comparative Example 2 Step 1: weigh 1 kg of polycrystalline positive electrode material LiNi with a median particle size D50 of 12 μm. 0.625 Co 0.065 Mn 0.31 O2.
[0134] Step 2: weigh 300 g of polycrystalline positive electrode material LiNi with a particle size of 6.5 μm. 0.625 Co 0.065 Mn 0.31 O2.
[0135] Step 3: Mix the two polycrystalline positive electrode materials evenly with a mixer to obtain a final positive electrode material.
[0136] Comparative Example 3 Step 1: weigh 1 kg of single crystal ternary precursor Ni prepared by coprecipitation method. 0.625 Co 0.065 Mn 0.31 O x (0.5<X<1.5), 503.6g lithium carbonate, after mixing evenly, heat-treat at 880℃ in oxygen atmosphere for 10h to obtain an intermediate product.
[0137] Step 2, weigh 300 g of the intermediate product and 10 g of cobalt oxide, mix them thoroughly, place them in an atmosphere furnace, keep them at 800° C. for 5 h, and then cool them to room temperature to obtain a positive electrode material matrix.
[0138] Step 3: After the above cathode material matrix is fully dispersed with a mixer, 200 g of the cathode material matrix is mixed with 2 g of boric acid, transferred to an atmosphere furnace, and heat treated at 550 ° C for 5 h to obtain a cathode material LiNi 0.625 Co 0.065 Mn 0.31 O2.
[0139] Step 4: Mix the above positive electrode material with 1 kg of polycrystalline positive electrode material LiNi with a particle size of 12 μm. 0.625 Co 0.065 Mn 0.31 O2 is mixed evenly to obtain the final positive electrode material.
[0140] The following method was used to perform performance tests on the positive electrode materials obtained in the above Examples 1-17 and Comparative Examples 1-3.
[0141] 1. Use Mastersizers 3000 to characterize the particle size distribution and volume distribution of the material: The particle size test method refers to GB / T 19077-2016. It can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0142] In the particle size distribution spectrum of the positive electrode material, the particle size distribution width function of the two peaks and Expressed as: (1), in, They are the particle size ratio parameters of the second peak with x in the range of 1 μm-6 μm; (2), in, They are the particle size number ratio parameters of the first peak in the range of 0.1μm-2μm.
[0143] The particle size volume distribution is measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK. Dv10 represents the particle size corresponding to 10% of the cumulative particle size distribution percentage of the powder, Dv50 represents the particle size corresponding to 50% of the cumulative particle size distribution percentage, and Dv90 represents the particle size corresponding to 90% of the cumulative particle size distribution percentage.
[0144] 2. Specific surface area characterization: Equipment: Specific surface area and pore structure analyzer.
[0145] Method: Weigh the mass of the empty sample tube m1; take 3g of sample and add it to the sample tube through a long-necked funnel; vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; the mass of the sample is m=m2-m1. The sample tube is placed in liquid nitrogen, and the nitrogen adsorption amount V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm. Among them, P / P0 is set to 0.05 / 0.1 / 0.15 / 0.20 / 0.25 / 0.30. Fit the isothermal adsorption curve, calculate the monolayer saturated adsorption amount Vm according to the slope and intercept, and then calculate the specific surface area according to Vm.
[0146] 3. Compacted density characterization: Using the American Carver 4350 tester, 1g of sample was weighed and placed in a mold, pressed with a pressure of 3T for 30s. After pressing, the height was tested and the compacted density was calculated.
[0147] 4. Characterization of powder conductivity: Equipment: ST2722-SZ powder resistivity tester is used.
[0148] Method: Take the powder sample and add it to the feeding chamber until it is full and slightly overflowing, then use a small spoon to slightly compact and flatten it; turn the hand wheel counterclockwise to press down the upper electrode; pressurize in stages until the pressure is 6T, and read the pressure of the pressed powder on the panel of the test instrument as 6T. The powder resistivity is the powder resistivity under 6T pressure. The powder conductivity under 6T pressure is the reciprocal of the powder conductivity under 6T pressure.
[0149] 5. Average grain size test: Hitachi S4800 scanning electron microscope was used to take 5 views of the sample at different positions at 3000 times magnification, and Nano Measure software was used to measure the primary particle size of the positive electrode material in the view. The average value of the 5 particle sizes was taken as the average particle size D of the primary particles.
[0150] 6. Test of metal element content in positive electrode materials: The content of various metal elements in the positive electrode material was tested by ICP. The element content in the material was analyzed using an Agilent 5800 ICP spectrometer. The specific operation steps were as follows: 0.4 g of ternary positive electrode material was added to a conical flask, and then 60 mL of pure water and 8 mL of aqua regia were added. The flask was placed on a graphite heating platform and digested at 375 ° C until it was clear. The obtained solution was diluted to 100 mL using a volumetric flask and sampled for dilution, and then the diluted solution was analyzed for composition.
[0151] 7. Battery production and performance testing: a. Preparation of electrochemical performance test samples: Button battery production: ① Ingredients: NCM: SP: 5% PVDF glue = 93: 5: 2 = 9.3 g: 0.5 g: 4.0 g, NMP=9g, stir at high speed to disperse evenly.
[0152] ② Coating and drying: Evenly coat the slurry on 20μm thick aluminum foil with a 210um coater, set the coating length to the maximum length of the coater, cut the back half of the electrode and put it into a 100℃ forced air drying oven to dry for more than 1.5 hours.
[0153] ③ Rolling, punching and drying: When rolling, adjust the roller machine to 1 roller gap and roll 3 times; use a 14mm punching machine to punch holes, weigh, and place in a vacuum drying oven for vacuum drying at 85°C for more than 8 hours.
[0154] ④ Button battery (LIR2016) assembly: positive electrode shell - 2 drops of electrolyte - positive electrode sheet (14mm) - 3 drops of electrolyte - 20μm diaphragm - 2 drops of electrolyte - φ16*1.0mm lithium sheet - 150μm nickel foam - negative electrode shell (dried at 50℃). After the battery is assembled, seal it and take it out of the glove box for testing.
[0155] b. Power-off test: After standing for 12 hours, perform the battery test according to the following system: 0.1C charge and 0.1C discharge for 2 weeks, constant voltage cut-off current 0.005C, the first cycle capacity and the first cycle coulombic efficiency were measured.
[0156] 0.5C charge and 2C discharge for 1 week, constant voltage cut-off current 0.05C, the ratio of the measured capacity to the first cycle capacity is the 2C capacity retention rate; The battery was cycled at 0.5C charge and 1C discharge for 50 cycles with a constant voltage cutoff current of 0.05C. The ratio of the measured capacity to the first cycle capacity is the capacity retention rate after 50 cycles.
[0157] 0.1C charge and 0.1C discharge to 3.7V, after standing for 5h, put the battery in -20℃, then discharge at 2C for 30s, take a point every 0.1s, and calculate the average internal resistance of 30s as the low temperature DCR (DC internal resistance); After standing at 60℃ for 30 days, charge at 0.1C and discharge at 0.1C for 1 week, with a constant voltage cutoff current of 0.05C; the ratio of the measured capacity to the first cycle capacity measured at 0.1C is the high temperature capacity retention rate; Charge at 0.1C and discharge at 0.1C to 3.7V. After standing for 5h, place the battery at 60℃ and discharge at 2C for 30s. Take a point every 0.1s and calculate the average internal resistance of 30s as the high-temperature DCR (DC internal resistance). Subtract the low-temperature DCR from the high-temperature DCR and divide it by the low-temperature DCR test result to get the DCR growth rate.
[0158] The corresponding test results of the positive electrode materials of Examples 1-17 and Comparative Examples 1-3 are shown in Tables 1 to 3 below.
[0159] Table 1 Note: 1. X2 is the horizontal coordinate corresponding to the first peak, X1 is the horizontal coordinate corresponding to the second peak, X2 peak percentage indicates the peak percentage of the first peak, X1 peak percentage indicates the peak percentage of the second peak, and peak percentage represents peak intensity. The larger the value, the greater the peak intensity, indicating that the peak is sharper.
[0160] 2. Peak intensity ratio = X2 peak percentage / X1 peak percentage.
[0161] 3. a is the diameter distance of the second peak, and b is the diameter distance of the first peak. The so-called diameter distance is [(D90-D10) / D50]. Separate the two peaks and calculate the diameter distance of each to obtain the distribution widths Span(a) and Span(b) of the two peaks.
[0162] Table 2 Table 3 Figures 3 to 6 The SEM photos of the positive electrode materials of Examples 1-4 are shown in Figure 1. Figures 3 to 6 It can be seen that the positive electrode material particles of Examples 1-4 are evenly dispersed, and the gaps between large particles are evenly filled with micro-powdered particles. The particles are densely packed, which effectively improves the compaction density of the positive electrode material, enables the material to obtain a higher volume capacity density, and thus increases the capacity of the prepared battery. At the same time, the dense packing of particles also helps to improve the ionic conductivity of the positive electrode material, so that the material obtains a higher powder conductivity.
[0163] Figure 7 is the particle size distribution curve of the positive electrode material of Example 1, combined with Figure 7 It is further proved that the particle size distribution curve of the positive electrode material in Example 1 presents a bimodal feature, wherein the first peak is between 0 and 2 μm, belonging to the particle peak of the micro-powder state, and the second peak is between 1 μm and 6 μm, belonging to the main particle peak of larger particles.
[0164] It can be seen from Table 1-3 that in Examples 1-17, the positive electrode materials all have high powder conductivity, and the prepared batteries have high capacity and good cycle performance, wherein the powder conductivity T of the positive electrode material is greater than 0.015S / cm, the capacity of the prepared battery is greater than 200mAh / g, the first cycle coulomb efficiency is greater than 90%, the 50-cycle capacity cycle retention rate is greater than 94%, the 2C capacity retention rate is greater than 86%, the low-temperature DCR is less than 126Ω, and the high-temperature DCR growth rate is less than 11%. This is mainly because, in Examples 1-17, the positive electrode material obtains a higher powder conductivity, and the higher powder conductivity makes the positive electrode material have good conductivity, effectively reduces the resistance and power consumption of the prepared battery, and improves the efficiency of energy transmission. Secondly, in Examples 1-17, the particle size distribution curve of the positive electrode material is limited to present the above bimodal characteristics, and controllable small particles in a micro-powder state are introduced, so that the positive electrode material has the advantages of high compaction density and high material activity at the same time, and solves the problems faced by existing positive electrode materials, such as the uncontrollable number of particles in a micro-powder state leading to increased surface side reactions and increased gas production, thereby improving safety and cycle performance. In addition, the introduced small particles in a micro-powder state can also be used as a buffer in the positive electrode material to disperse stress and suppress the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material. Therefore, the high compaction and high ionic conductivity brought about by the high packing density of the positive electrode material of Examples 1-17 complement each other, so that the battery prepared from the positive electrode material has both high capacity and energy transfer efficiency, low resistance and power consumption, and excellent cycle performance.
[0165] Specifically, in Examples 1-3, the particle size of the precursor particles can be controlled by adjusting the nozzle pressure and the nozzle diameter, so that the particle size distribution curve of the positive electrode material presents a bimodal feature. With the increase of the nozzle pressure / nozzle diameter (i.e., the pressure-diameter ratio), the number of small-sized particles increases, the conductivity of the powder increases, the capacity and cycle performance of the prepared battery do not change much, but the low-temperature DCR decreases.
[0166] However, the positive electrode material prepared by the coprecipitation method in Comparative Example 1 has a particle size distribution curve that is not bimodal, but has only one large particle. The powder has a low conductivity, the capacity of the prepared battery is low, and the cycle performance is poor. Although Comparative Example 2 has a bimodal structure, it is a polycrystalline material and does not meet the following requirements: the first peak is between 0 and 2 μm, the second peak is between 1 μm and 6 μm, the overall particle size is large, the powder has a low conductivity, and the cycle performance of the prepared battery is poor. The positive electrode material prepared by the coprecipitation method in Comparative Example 3 is difficult to form single crystal particles with good dispersibility, the powder has a low conductivity, and the cycle performance of the prepared battery is poor.
[0167] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The particle size number distribution curve of the positive electrode material includes a first peak and a second peak, the first peak is located between 0 and 2 μm, the second peak is located between 1 μm and 6 μm, and the first peak is located on the left side of the second peak; the powder conductivity T of the positive electrode material under a pressure of 6 T satisfies: T>0.015S / cm.
2. The positive electrode material according to claim 1, characterized in that The intensity ratio of the first peak to the second peak is ≥ 1.5; and / or, The ratio of the peak areas of the first peak to the second peak is 0.1-1.
3. The positive electrode material according to claim 1, characterized in that The powder conductivity T of the positive electrode material under a pressure of 6T satisfies: 0.015S / cm<T<0.05S / cm.
4. The positive electrode material according to claim 1, characterized in that The XRD diffraction spectrum of the positive electrode material includes a 003 peak and a 104 peak, and the peak intensity ratio of the 003 peak to the 104 peak is 1.1-1.
8.
5. The positive electrode material according to claim 2, characterized in that The intensity ratio of the first peak to the second peak is 1.5-4.
6. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is as follows: Li a Ni x M y N 1-x-y O b , wherein 0.98≤a≤1.05, 0.60≤x<1, 0<y≤0.40, 0.95≤b≤1.05, the M element is selected from at least one of Co, Mn and Al, and the N element is selected from at least one of Ti, Zr, Mg, Sr, Ba, Nb, W and Y.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) In the volume particle size distribution of the positive electrode material, D50 is 2.5 μm to 5.5 μm, Dmin>0.1 μm, and Dmax<14 μm; (2) The volume particle size distribution width of the positive electrode material is 1.0~2.6; (3) The specific surface area of the positive electrode material is 0.6 m 2 / g~1.2m 2 / g; (4) The compaction density of the positive electrode material is greater than 3.0 g / cm 3 ; (5) The powder resistivity of the positive electrode material under a pressure of 6T is less than 6666.66Ω·m.
8. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the positive electrode material contains single crystal grains with the same orientation, and the average grain size of the single crystal grains is 1 μm to 6 μm.
9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 8.